Deletion of AIF1 but not of YCA1/MCA1 protects Saccharomyces cerevisiae and Candida albicans cells from caspofungin-induced programmed cell death - Christopher Chin; Faith Donaghey; Katherine Helming; Morgan McCarthy; Stephen Rogers; Nicanor Austriaco (Microbial Cell)
Caspofungin was the first member of a new class of antifungals called echinocandins to be approved by a drug regulatory authority. Like the other echinocandins, caspofungin blocks the synthesis of β(1,3)-D-glucan of the fungal cell wall by inhibiting the enzyme, β(1,3)-D-glucan synthase. Loss of β(1,3)-D-glucan leads to osmotic instability and cell death. However, the precise mechanism of cell death associated with the cytotoxicity of caspofungin was unclear. We now provide evidence that Saccharomyces cerevisiae cells cultured in media containing caspofungin manifest the classical hallmarks of programmed cell death (PCD) in yeast, including the generation of reactive oxygen species (ROS), the fragmentation of mitochondria, and the production of DNA strand breaks. Our data also suggests that deleting AIF1 but not YCA1/MCA1 protects S. cerevisiae and Candida albicans from caspofungin-induced cell death. This is not only the first time that AIF1 has been specifically tied to cell death in Candida but also the first time that caspofungin resistance has been linked to the cell death machinery in yeast.